Perancangan Kandang Pintar Menggunakan NodeMCU ESP32 dan Platform Blynk - Erik Agustian Yulanda; Rizki Kurniawan (CV. Multi Kreasi Media, 2024)
Pet owners, especially cat owners, often face difficulties in providing regular feeding due to their daily busy schedules. Irregular feeding can have serious impacts on the physical and behavioral condition of animals, such as malnutrition, stress, and depression. The solution to this problem is the utilization of IoT-based smart cages that enable effective monitoring of pet conditions. These smart cages are equipped with an IoT system that facilitates pet owners in monitoring their animals' well-being. To maintain an ideal temperature within the cage, a DHT22 sensor is used to automatically control the temperature. Additionally, the availability of food and water in the cage is monitored through an ultrasonic sensor integrated with the Blynk application. Prior to implementation, testing and calibration are conducted on each sensor. The test results indicate high levels of accuracy: 98.53% for the temperature sensor (DHT22), 98.82% for the ultrasonic sensor, and 98.89% for the water level sensor. This signifies the good quality and performance of the developed system. Apart from cage condition monitoring, this system also allows pet owners to directly view live video streaming from the cage through the Blynk application. The monitoring process involves the NodeMCU ESP32 microcontroller, which transmits data to the Blynk application over the internet.